Penggunaan Balon Udara untuk Tujuan Spionase dan Implikasi Terhadap Hukum Internasional - Atmodjo, Kevin Christian; Wattimena, Josina Augustina Yvonne; Peilouw, Johanis Stenly Franco (PATTIMURA Law Study Review, 2025)
This research analyzes a violation of airspace sovereignty by unmanned free balloons for espionage purposes. Each country has full and exclusive sovereignty over its entire territory which includes the surface of the earth and the contents of the earth beneath the surface, including air space. A country that violates sovereignty over airspace without permission entails responsibility for the passing country towards the lower country. The research method used is normative juridical using problem approaches such as the statute approach, conceptual approach, and case approach. The research findings show that unmanned free balloons are the same as the classification of aircraft regulated in Annex 2 of the 1944 Chicago Convention regarding unmanned free balloons which are defined as unpowered, unmanned, and lighter than air aircraft in air flight. The use of unmanned free balloons for espionage purposes in peacetime has no legal regulations, so that they have implications for violations of state sovereignty which give rise to state responsibility. ICAO or International Civil Aviation Organization needs to reconstruct the legal ground towards unmanned free balloons usage outside the function of meteorological purposes in order to avoid the false accused and declare specified sanctions towards the violators.